Analisis Sentimen Masyarakat terhadap Teroris dalam Media Sosial Twitter menggunakan NLP - Shobrina Fathoniah; Chaerur Rozikin (Jurnal Ilmiah Wahana Pendidikan, 2022)
The use of social media is not only to communicate between humans and other humans, but nowadays, social media can be a place to exchange ideas about various things, such as Twitter social media. Twitter is widely used in Indonesia to discuss various things that are currently happening or phenomenal events such as terrorism. So that an analysis of public sentiment against terrorism can be carried out on Twitter using NLP and LSTM. The use of NLP for preprocessing data is to remove urls and mentions and tokenization of tweet sentences. Meanwhile, the use of LSTM when modeling can provide an accuracy rate of 59.34% with a unit value of 20.